Evaluasi Emergent Strategy Bisnis PLTS Atap PT X sehubungan dengan Ketidakpastian Strategis Permintaan Pasar - Sutopo, Primisita; Rossieta, Hilda (Jurnal Manajemen dan Organisasi, 2023)
PT X is one of the developers of rooftop solar photovoltaic (PV) power plants in the commercial and industrial sectors in Indonesia. Over time, there has been a strategic uncertainty of market demand since 2022, mainly affected by the strong bargaining position of Wilayah Usaha's state-owned enterprise (Wilus SOE). Wilus SOE plays a significant role, is given priority in the provision of electricity for the public interest as stipulated in the regulation, and also has a dominant share (95 percent in 2020), making it a de facto monopoly in the electricity business in Indonesia. Wilus SOE has legitimacy as a power distributor and therefore has the authority to approve the capacity of rooftop solar PV power plants. Referring to this situation, this research aims to identify the intended strategy of PT X and the emergent strategy in dealing with the strategic uncertainty of market demand. PESTEL analysis (political, economic, sociocultural, technological, environmental, legal) and five-forces framework (competitive rivalry, new entrants, substitute products, suppliers, customers), as well as emergent strategy evaluation, were used as the framework of this research. To strengthen the analysis results, in-depth interviews were also conducted with the management team of PT X. Based on the series of analyses, it can be concluded that PT X's business is strongly influenced by legal factors while the competitive rivalry and customers' factor have very strong forces. On the other hand, PT X has implemented an emergent strategy well in dealing with the strategic uncertainty of market demand, as an effort to maintain the company's profitability. This research is expected to provide benefits for PT X and other rooftop solar PV power plant developers to understand the emergent strategy in order to remain competitive in its business implementation.